Pengaruh Karakteristik Pekerjaan dan Motivasi Kerja terhadap Kinerja Guru: Peran Mediasi Ketangkasan Digital dan Peran Moderasi Dukungan Organisasi yang Dirasakan di Sekolah Menengah Kejuruan Ketintang Surabaya - Yahya Kurnia Hanjaya; Ida Aju Brahma Ratih; Abdul Halik (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to investigate the determinants of teacher performance in the vocational education sector, focusing on job characteristics and work motivation as the main antecedents. This study also examines the mediating role of digital dexterity and the moderating effect of Perceived Organizational Support (POS). An explanatory quantitative approach was adopted using Partial Least Squares-based Structural Equation Modeling (SEM-PLS). The research population and sample were all teaching staff at SMK Ketintang Surabaya, totaling 91 people (a saturated sample). Data was collected through questionnaires and processed using SmartPLS 3.0. The findings indicate that job characteristics and work motivation have a significant effect on digital dexterity and teacher performance. Digital dexterity was proven to mediate this influence. Specifically, Perceived Organizational Support (POS) was also shown to significantly moderate the relationship between digital dexterity and teacher performance. These results provide a theoretical contribution, showing that job design and organizational support influence performance in the era of digital transformation. A practical implication that can be applied is the importance of schools providing tangible support and autonomous job design to maximize teachers' digital competencies.